Dejanje v začetku - Snoj, Vid (Primerjalna književnost, 2003)
Deed in the beginning. The first part of the text is a reading of the Biblical narrative of creation, which attempts to demonstrate the sublimeness of both the event itself and the narrative. The second part is a discussion of the implications of the narrative for European science and poetry.
Keywords: Biblia; Bible; Sveto pismo; interpretacije; stvarjenje; literarno ustvarjanje; pesništvo; pesniški jezik